Prediction and Understanding of Resilience in Albertan Families: Longitudinal Study of Disaster Responses (PURLS) – Protocol - Kingston, Dawn; Mughal, Muhammad K.; Arshad, Muhammad; Kovalchuk, Igor; Metz, Gerlinde A.S.; Wynne-Edwards, Katherine; King, Suzanne; Jiang, Shui; Postovit, Lynne; Wajid, Abdul; McDonald, Sheila; Slater, Donna M.; et al. (Frontiers in Psychiatry, 2019)
Exposure to a natural disaster in childhood can have serious, long-lasting consequences, impacting physical and mental health, development and learning. Although many children experience negative effects after a disaster, the majority do not, and what differentiates these groups is not well understood. Some of the factors that influence disaster-related outcomes in the midst of adversity include parents’ mental health, the home environment, and socioeconomic status. Furthermore, genetics has also a role to play in how children respond to stressors. We had the opportunity to conduct a natural experiment of disaster recovery following the Alberta 2013 Flood. This paper presents the detailed protocol on prediction of resilience in Albertan families, and validation with cortisol data. In addition, data collection procedures, developing resiliency screening tools, candidate gene identification, genotyping, DNA methylation and genomic analyses are described to achieve the research objectives. This study produced new knowledge by using pre- and post-disaster information on children's health and development, including children's genetics and responses to stress. This information has been identified as important to governments and other organizations invested in early child development. Our comprehensive research plan will generate evidence that can be mobilized population-based approaches to improve child and family resiliency.